2017
DOI: 10.1002/pbc.26586
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of cabozantinib in two pediatric patients with recurrent renal cell carcinoma

Abstract: Advanced-stage renal cell carcinoma (RCC) carries a dismal prognosis for pediatric patients with few studied therapeutic options. Cabozantinib is a small molecule tyrosine kinase inhibitor against the oncoprotein MET. It is currently approved by the U.S. Food and Drug administration for second-line treatment of RCC in adults. There is no published data on its use in children with RCC. We report here two pediatric patients with recurrent metastatic RCC whose tumors expressed MET and were treated with cabozantin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Selle et al reported the use of immunotherapy in four patients where one patient with ccRCC showed a complete response . More recently, Wedekin et al reported two patients with pRCC who responded to cabozantinib . Malouf et al reported eight cases of pediatric/young adult tRCC (ages 2–28 years, average 17.4 years), only four of which had measurable disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Selle et al reported the use of immunotherapy in four patients where one patient with ccRCC showed a complete response . More recently, Wedekin et al reported two patients with pRCC who responded to cabozantinib . Malouf et al reported eight cases of pediatric/young adult tRCC (ages 2–28 years, average 17.4 years), only four of which had measurable disease.…”
Section: Discussionmentioning
confidence: 99%
“…1,6 In review of the literature, 20 pRCC cases were identified where RCC-directed medical treatment is detailed with some outcome data included, the majority being individual case reports and small institutional reports . [24][25][26][27][28][29][30][31][32] Many of the reported pRCC cases include the administration of preoperative chemotherapy on the suspicion that the tumor was a Wilms tumor rather than pRCC. 33 Indolfi et al list immunotherapy as primary treatment for nine pRCC patients; however, no data are presented to demonstrate the effect of such therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of imatinib, an inhibitor of the BCR-ABL fusion tyrosine kinase, revolutionized the treatment of chronic myelogenous leukemia [218] and other leukemias expressing this fusion protein [219] . While these kinase inhibitors are generally designed for specificity for one kinase, often times they have effects on multiple kinases due to homology among the proteins, with varying toxicity and efficacy [220][221][222][223] . With these drugs, resistance often develops with time as well.…”
Section: New Therapies New Mechanisms Of Resistancementioning
confidence: 99%
“…Unfortunately, there are little to no treatments available for patients who are diagnosed with unresectable metastatic renal cell tumors, since radiation and chemotherapy are ineffective in this setting (De Pasquale et al, ; Ramphal, Pappo, Zielenska, Grant, & Ngan, ). Recent studies have begun to explore the efficacy of molecularly targeted therapies, and a recent report demonstrated that pediatric patients with TFE3 translocation renal cell tumors demonstrate improvement after treatment with the tyrosine kinase inhibitor, cabozantinib (Wedekind, Ranalli, & Shah, ). Interestingly, a recent clinical trial has shown that patients diagnosed with adulthood papillary RCC demonstrate response to cabozantinib (Campbell et al, ; Chanzá et al, ).…”
Section: Renal Cell Tumors: Most Common Renal Malignancies In Adultsmentioning
confidence: 99%